The Role of Burdah and Ngelenggang Religious Rituals in Preserving the Loloan Malay Language in West Bali - I Gusti Ayu Gde Sosiowati; Ni Luh Nyoman Seri Malini; Putu Wahyu Widiatmika; Miina Norvik; Nissa Puspitaning Adni (Universitas Udayana, 2025)
Loloan Malay is an endangered indigenous language which is also the identity of a minority Muslim community in Jembrana, West Bali. In the midst of the strong Hindu influence in Bali, the Loloan people try to maintain their different linguistic and cultural heritage through oral traditions such as Burdah and Ngelenggang—ritual performances presenting religious verse recitations accompanied by percussion performed during a seven-month pregnancy. This study aimed to explore how Loloan Malay language as their identity is maintained through Burdah and Ngelenggang rituals. Data were collected through interviews and observations, focusing on community leaders, ritual performers, and youths. The findings revealed that conducting the rituals maintains the language through the cultural materials and communication. Furthermore, the research also unpacks the language of having inconsistency in orthography, which affects not only the written communication but also the education. This study implies that sustainable religious practices can be markers of how well languages are maintained.